Corporate governance and the African business context: the case of Nigeria - Letza, Steve (Economics and Business Review, 2017)
A robust institutional framework is essential to enable fi rms to function efficiently. The aspect of corporate governance investigated in this paper is the legal and societal principles and process which form the business context within which firms operate. The paper explores the challenges to firms trading in Africa arising from cultural dynamics peculiar to the continent and further explores the historical reasons for the present cultural context to business in Africa. Nigeria is presented as a special case, perhaps even an extreme case, of the challenges to corporate governance in Africa since it is perceived by many to be one of the weaker environments given its perceived levels of corruption. The paper concludes with an assessment of the likelihood of African states successfully tackling corruption in the future as the current approaches unfold over the coming years.